Hubungan Konsep Diri Dan Kecemasan Komunikasi Interpersonal Pada Mahasiswa Bimbingan Dan Konseling Angkatan 2020 Universitas Sanata Dharma Yogyakarta - Widiyati, Cicilia; Setyandari, Anastasia (Universitas Sanata Dharma, 2023)
This study aims to: 1) describe the level of self-concept in students of Guidance and Counseling Study Program class of 2020, Sanata Dharma University Yogyakarta; 2) describe the level of interpersonal communication anxiety in students of Guidance and Counseling Study Program class of 2020, Sanata Dharma University Yogyakarta; 3) analyze how much the relationship between self-concept and interpersonal communication anxiety in students of Guidance and Counseling Study Program class of 2020, Sanata Dharma University Yogyakarta.The type of research is quantitative correlation. The research subjects were students of the Guidance and Counseling Study Program class of 2020, Sanata Dharma University Yogyakarta, totaling 115 students. This study used purposive sampling technique. Data collection uses a self-concept scale and an interpersonal communication anxiety scale.The results showed that: 1) 6 students (9.4%) had a very high level of self-concept, 28 students (43.8%) had a high level of self-concept, and 30 students (46.9%) had a moderate level of self-concept; 2) 1 student (1.6%) had a very high level of interpersonal communication anxiety, 16 students (25%) had a high level of interpersonal communication anxiety, 44 students (68.8%) had a moderate level of interpersonal communication anxiety, and 3 students (4.7%) had a low level of interpersonal communication anxiety; 3) There is a significant positive relationship between self-concept and interpersonal communication anxiety with the results of the Spearman's rho analysis test, namely rxy = 0.579 with a significance of p = 0.000 (p 0.05, so the level is significant). The results of this study are not in line with the hypothesis built so that it is discussed in the limitations of the study